The effect of the acquirers' market capitalization and payment method on the short-term return of M&As in Greater China and South Korea - Kimberley Jasmijn Rijskamp (The Central European Review of Economics and Management (CEREM), 2023)
Aim: The main goal of this paper is to gain insights into the effect of the market capitalization of the acquirer and the method of payment utilized on the short-term return of the acquiring firm, for deals made between a buyer and target in Greater China (including Hong Kong) and/or South Korea. Additionally, differences between these geographical areas and differences in the acquirer's industry are analyzed. Design / Research methods: Data was retrieved from Refinitiv's EIKON database. A total of 462 deals was obtained and analyzed, using a nested methodology combining elements of an event study with regression analyses. Conclusions / findings: Acquirers with a small market capitalization obtain either more negative or more positive CARs as compared to large market capitalization acquirers. Secondly, no significant evidence is found that paying a deal using solely cash results in higher CARs as compared to paying a deal fully in shares. Interestingly, it is found that in South Korea paying a deal using shares results in statistically significant higher CARs. Moreover, in China negative CARs tend to be more extreme. Lastly, acquirers operating in the Media and Entertainment industry and in the field of High Technology generate higher CARs. Originality / value of the article: This paper provides insights into the effects of market capitalization and the payment method in the context of Greater Chinese and South Korean M&As, which thus far have been little studied. Moreover, it uses a nested approach, combing elements from an event study with regression analyses.
Keywords: G34; 330; Mergers and Acquisitions; Cumulative Abnormal Return; Market Capitalization; Payment Method; Greater China; South Korea; Media & Entertainment; High Technology